2017
DOI: 10.3389/fpls.2017.02175
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Calmodulin-Like Proteins, CML15 and CML16 Possess Biochemical Properties Distinct from Calmodulin and Show Non-overlapping Tissue Expression Patterns

Abstract: Calcium ions are used as ubiquitous, key second messengers in cells across eukaryotic taxa. In plants, calcium signal transduction is involved in a wide range of cellular processes from abiotic and biotic stress responses to development and growth. Calcium signals are detected by calcium sensor proteins, of which calmodulin (CaM), is the most evolutionarily conserved and well-studied. These sensors regulate downstream targets to propagate the information in signaling pathways. Plants possess a large family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
(125 reference statements)
4
22
0
Order By: Relevance
“…CMLs regulate downstream targets in response to various stimuli-induced Ca 2+ fluctuations and signal transduction [ 14 ]. In Arabidopsis , CML15 and CML16 show changes in electrophoretic mobility in the presence of Ca 2+ , which confirms their ability to bind Ca 2+ [ 15 , 16 ]. The roles of CMLs in plant development and stress responses were investigated [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 88%
“…CMLs regulate downstream targets in response to various stimuli-induced Ca 2+ fluctuations and signal transduction [ 14 ]. In Arabidopsis , CML15 and CML16 show changes in electrophoretic mobility in the presence of Ca 2+ , which confirms their ability to bind Ca 2+ [ 15 , 16 ]. The roles of CMLs in plant development and stress responses were investigated [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 88%
“…In the case of CML14, the combination of ITC and NMR techniques has allowed for the demonstration that only one EF-hand can sense Ca 2+ ions, despite the presence of three EF-hand motifs [ 34 ]. Moreover, ITC analysis demonstrated that CML15 and CML16 contain only two and three functional Ca 2+ -binding sites, respectively, out of the four predicted EF-hands [ 35 ]. Therefore, caution should be used in functional predictions based only on sequence analysis ( Table 1 ).…”
Section: The Ef-hand: Variations On a Themementioning
confidence: 99%
“…Therefore, caution should be used in functional predictions based only on sequence analysis ( Table 1 ). In the absence of experimental 3D structures, homology models can be exploited as an alternative to support the presence of functional Ca 2+ -binding sites, as has been done for CML14 [ 34 ], CML15, and CML16 [ 35 ].…”
Section: The Ef-hand: Variations On a Themementioning
confidence: 99%
See 2 more Smart Citations